An Empirical Study of Ancient Wisdom. Effect of Anasakti (Non-Attachment) and Ahamkara (Ego) on Well-Being Amongst Indians - Gupta, Kriti; Agrawal, Jyotsna (European Journal of Mental Health, 2022)
Introduction: According to Indian psychology, anasakti (non-attachment) and ahamkara (ego) play a significant role in determining true happiness.Aims: To study the role of anasakti (non-attachment) and ahamkara (ego) on the level of well-being amongst Indian adults.Methods: For the current study, 240 educated, urban Indian adults (Females = 104, Males = 136) were surveyed to investigate the relationship of anasakti (non-attachment) and ahamkara (ego) with well-being variables.Results: Anasakti (“non-attachment”) was revealed to be a significant factor in ensuring life satisfaction and experiencing positive emotions. Although ahamkara (“ego”) contributed significantly toward higher cognitive well-being and affective states, it better predicted negative emotions.Conclusions: The current study’s findings may widen our understanding of “What makes people happy?” and may add to the global well-being literature.